Neutralization of local effects of the terciopelo (Bothrops asper) venom by blood serum of the colubrid snake Clelia clelia - Lomonte, Bruno (1982)
The neutralizing capacity of the blood serum of the non-venomous snake Clelia clelia against the hemorrhagic, edematous and myonecrotic effects of Bothrops asper venom in white mice was tested using in vitro preincubation experiments. Untreated serum neutralized to a different extent all local effects evaluated, but showed toxicity to mice, evidenced by edema and myonecrosis. Serum heated at 56°C for 30 min lost its toxic properties but also its neutralizing capacity against hemorrhagic and edematous effects of the venom. The myonecrotic effect was neutralized by large quantities of heated serum. The serum of C. clelia formed a single precipitation arc in immunoelectrophoretic slides against B. asper venom, corresponding to the slow anodic proteins of the serum.